Pengaruh faktor pengali asimetri terhadap kapasitas beban angkat perempuan Indonesia - Kurnianingtias, Mayesti; Ardiyanto, Ardiyanto (Universitas Gadjah Mada, 2023)
Manual material handling can improve occupational diseases such as low back pain and musculoskeletal disorders. In an attempt to reduce the risk of injury as a result of such work, NIOSH published the recommended weight limit (RWL) equation. The RWL formulation was made with Europeans and Americans, so this research was conducted to see the suitability of the RWL formulation for Asians, especially Indonesians. The participants of this study were 30 Indonesian women students. The independent variable in this research is the asymmetry multiplier. The participants perform asymmetric lifting in 0, 30, 60, and 90 degrees with the frequency of 1 lift/min in a 30-minute duration. Other multiplier factors such as the vertical multiplier, distance multiplier, and coupling multiplier are made to have a value of 1. The weight of the load lifted by the respondent is adjusted to the maximum load that each respondent can lift comfortably, which is usually called the maximum acceptable weight of lift (MAWL). The heart rate data used for analysis is the heart rate in the last five minutes. In addition, respondents also filled out the Borg RPE scale. The results of this study were that the heart rate increased from an average resting heart rate of 83.12 beats/minute to 90.6 beats/minute. The statistical test results showed that there was no significant effect between asymmetry lifting tasks on heart rate, energy expenditure, and the Borg's Scale RPE (α = 0,05). Energy expenditure in this study is still below the threshold set by NIOSH. From this study, the predicted AM equation of physiological for Indonesian (energy expenditure) is AM = 1 - (0,0024A) and the predicted AM equation of RPE is AM = 1 - (0,0029A).